Solidarity, international human rights declarations and bioethics: the case of the right to health of aboriginal Colombian peoples - Bernal Camargo, Diana Rocío (Acta Bioethica, 2013)
This paper shows the role of the solidarity principle in relation to right to health of Colombian aboriginal peoples, analyzing the Universal declaration of the rights of aboriginal peoples and the Declaration on Bioethics and Human Rights. Current situation of these ethnic groups is presented as it relates to access to the highest levels of health, based on reports from United Nations and postulates of aboriginal peoples regarding the tight to health.The analysis evidences that the role of solidarity in this field should serve as an element for promoting traditional indigenous practices in order to integrate them to Western health systems. This would guarantee the access in equity and the strengthening of medical institutions without generating assimilation or exclusion in the access to the right to health.